Efficient discovery of potent α-glucosidase inhibitors from Paeoniae lactiflora using enzyme–MOF nanocomposites and competitive indicators. Issue 1 (8th December 2022) - Chen, Xinlin; Wu, Ying; Gu, Yucheng; Luo, Jianguang; Kong, Lingyi
Abstract : In the present study, to gain further insight into this plant and find out potent GAA inhibitors, a novel ligand fishing strategy based on competitive indicator and enzyme-MOF nanocomposites was established. Abstract : A great deal of attention has been paid to the seeds of Paeoniae lactiflora pall., an underutilized food resource, since its extract exhibits excellent α -glucosidase (GAA) inhibitory activity. In the present study, to gain further insight into this plant and find out potent GAA inhibitors, we established a novel ligand fishing strategy by introducing a competitive inhibitor as an indicator. After the successful establishment of this approach was verified by a series of methods, including kinetic assay, fluorescence determination, and HPLC, the newly developed ligand fishing method was applied to acquire potent GAA inhibitors from P. lactiflora seeds. Nine bioactive compounds were captured, and seven of them were identified as suffruticosol A, suffruticosol B, resveratrol, vitisin E, luteolin, trans -δ-viniferin, and ampelopsin E. The data of their GAA inhibitory activity demonstrated that these constituents were vigorously active against GAA with IC50 values of 1.67–30.47 μM, while such value of 1-DNJ was 228.77 μM. Among them, vitisin E and ampelopsin E were reported to show such inhibitory activity for the first time. Collectively, our findings provide valuable clues for the further utilization of P. lactiflora seeds as a functional food, and offer a new avenue for acquiring potent inhibitors from natural resources.